The effectiveness of elaboration and organizational strategies in science education on students' academic achievement, attitude and concept learning - (:unkn) unknown (My University, 2013)
The aim of this study is to determine the effectiveness of using elaboration and organizational strategies in science education on students' academic achievement, attitude and concept learning. In the study, both quantitative and qualitative research methods were used. In quantitative part, the quasi-experimental matching only pretest-posttest control group design was used. In qualitative part, data was obtained through document analysis. The research was conducted with 120 6 th grade students (2 experimental groups and 1 control group) in a public elementary school in the district of Bagcilar during 2009-2010 academic year. The treatment process took 30 class hours. Three instruments namely academic achievement test, attitude towards science scale and open ended questions were used during the treatment process. The reliability coefficient of the academic achievement test was calculated as KR20=.88. The Cronbach alpha value of the attitude towards science scaled which was developed by Akinoglu [1] was found as α=.89. The open-ended questions were used in order to ass concept learning. On the basis of collected data through the treatment it was indicated that the implementation of learning strategies namely elaboration and organizational strategies into learning process affected students' academic achievement, attitude towards science positively. Also it was found using elaboration and organizational strategies in science education affected students' conceptual learning positively and reduced the number of misconceptions that they had hold. © Sila Science.
Keywords: Attitude; Concept learning; Learning; Learning strategies; Science education